Clinical and Epidemiologic Description of Orofacial Clefts in Bogota and Cali, Colombia, 2001-2015. (April 2018) - Sarmiento, K.; Valencia, S.; Gracia, G.; Hurtado-Villa, P.; Zarante, I.
Objectives: Among congenital craniofacial anomalies, orofacial clefts (OFCs) are the most common. Global prevalence is 2 in 1000 and in Colombia, 1 in 700. Our goal was to describe cleft palate (CP) prevalence and cleft lip with or without cleft palate (CL±P) from 2001 to 2015 in Bogota and Cali, Colombia. Method: Using the ECLAMC case-control design method, information was obtained from the Congenital Anomalies Monitoring and Surveillance Programs in Bogota and Cali. We describe the prevalence of cases classified into the following groups: isolated, polymalformed, and syndromic. The proportion of cases and controls was 1:4. Data were analyzed using frequency distribution and Student t test to compare means and 95% confidence intervals (CIs). Results: We identified 529 OFC cases and 2116 controls from 448, 930 births: a rate of 11.8 per 10, 000 (CI = 10.80-12.83). From the total cases, 73% were identified with CL/CP compared to 27% with CP. Males had higher CL±P (59%) prevalence, whereas the highest neonatal mortality was observed among polymalformed cases (7%). The most common anomaly identified among our cases was cleft lip without isolated cleft palate (58%). We found that OFCs are linked to birthweight, size, and gestational age and higher parity with statistically significant differences in all variables compared to controls. Conclusions: OFC is a highly prevalent anomaly in Colombia, with a range of maternal and infant differences across case subgroups. The identification of important OFC subgroups that follow certain patterns of prevalence may prove useful to primary and tertiary care facilities with the goal of reducing further disability.